DAMPAK PROGRAM SMART-FISH UNIDO-KKP TERHADAP SEKTOR PERIKANAN INDONESIA (Rumput Laut, Patin, dan Tuna) - Rifdah Hanun A; Indra Pahlawan (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2020)
Indonesia is an archipelago country that has big potential in fishery sector. Seaweed, Catfish, Pole and Line Tuna cultivation is a concern of the government because of the high level of production. However, Indonesian fishery sector still has some shortcomings such as, low meat quality and not in accordance with international standards, high production cost, and low level of competitiveness in the global market. The Indonesian government through the MMAF is working with UNIDO (United Nations Industrial Development Organization) in a program called SMART-Fish Indonesia to overcome these problems.This qualitative research is document analysis using data from books, journals, newspapers and websites such as www.unido.org and www.kkp.go.id to describe impact of SMART Fish Program UNIDO and MMAF to Indonesian Fishery Sector. Group level analysis with neoliberalsm perspectives about the role of international organization and international organization theories was used to elaborate the impact.The result showed that SMART Fish Indonesia program succeeded in improving the performance of Indonesian fishery sector especially in seaweed, catfish, and tuna cultivation. The program succeeded in improving fish quality, lowering production costs, and increasing production profits. In addition, with this program, Indonesian catfish have their own brand named Indonesian Pangasius The Better Choice and have been known by many countries. Keywords: Fishery, UNIDO, SMART-Fish, MMAF, Cultivation